Educação, tecnologias e gênero: uma reflexão sobre o androcentrismo na tecnologia - Silva, Jane Reolo da (2017)
This research is inserted in the line of research New technologies in the education of the program of Post-Graduation in Education: Curriculum, of the Pontifical Catholic University of São Paulo. Since the 1980s, women have advanced quantitatively in academia and the labor market. However, in the courses and professions of Science, Technology, Engineering and Mathematics ( STEM) the female presence does not exceed twenty percent. This research aims to reflect on the causes of this gender inequity. This research started with the question: What are the causes of gender inequity in Science, Technology, Engineering and Mathematics (STEM), according to the activists' view of women's inclusion in technology development? It was based on an author-based framework with approaches on the role of gender as an element of analysis of interpersonal relationships such as Scott and Colling. The authors Boix and Natansohn were fundamental for the reflection on gender and technology. Other authors have contributed to the approach of gender relations in basic education such as Auad, Moreno and Lins Machado e Escoura, who analyze the role of education in the construction of a culture in basic education that establishes hierarchies and barriers in gender relations. Vieira-Pinto discusses the use of technology as an instrument of power and Paulo Freire points to the issue of education as an instrument of empowerment in a perspective of deconstructing injustices in gender relations. The methodological trajectory followed the qualitative approach of an interpretative nature. To answer the problem question of this research were conducted interviews with teachers of educational institutions of various STEM courses involved in the Digital Girls Program, an organization that develops training actions, aiming to bring girls closer to the context of computer programming and the STEM area. Research on the interrelationships between gender, technology and curriculum made it possible to identify, among the coincidences of the limitations to the participation of girls as technology developers, patterns of behavior present in the narratives of the research subjects. These patterns were categorized into concrete expressions of gender relations: sexism, misogyny, stereotypes, and gender expectations. A relation was established about the presence in the hidden curriculum of the basic education of a learning of the separation, through daily situations that reproduce the categorized expressions. We conclude through the data collected cultural aspects of gender relations as conditioners of the non-academic and professional choice of women in the area of technology. We point out the need for consideration by public and social policies, as well as the formative processes of educators, the reflection of gender relations in the basic education curriculum